'It's just the nature of the work': Barriers and enablers to the health and well‐being of preconception, pregnant and postpartum working women in a community service organisation. (30th October 2022) - Madden, Seonad K.; Blewitt, Claire; Hill, Briony; O'Connor, Amanda; Meechan, Donna; Skouteris, Helen
Abstract: Poor lifestyle practices, combined with excess weight gain and weight retention during the preconception, pregnancy and postpartum periods can increase health risks for mothers and their children. Little is known about how workplaces impact the health and well‐being of women of child‐bearing age, particularly across work roles and settings. This qualitative descriptive study explored the enablers and barriers to the healthy lifestyle practices and well‐being of women of reproductive age within an Australian community services organisation by capturing the perspectives of both the women and workplace executives. Eleven interviews were conducted with executives ( n = 12), and three focus groups and three interviews were conducted with women ( n = 16). Data were thematically analysed, and six main themes were identified: blurring of the role and work environment, clarity and equity in policy and entitlements, the nature of community services work, individual responsibility for health, tiered levels of support and a management‐driven culture of awareness and support. Barriers included high‐stress roles, work targets, sedentary work behaviours, lack of clarity around policies, funding and the emotional labour associated with community services work. Hands‐on leadership, open communication, work relationships, resourcing and manager training were identified as facilitators. While findings indicate agreement between executives and the women, many executives focused on the challenges associated with pregnancy in the high‐risk workplace environment and did not perceive specific barriers for those in non‐frontline roles. Management education to generate an understanding of women's needs during this life stage and increased resourcing to facilitate workplace well‐being would be beneficial.